Risk management and architecture design in securing cloud platforms: Case study of cloud models - Nevalainen, Samuli (My University, 2022)
Utilization of cloud environment has become more relevant for different companies and industries and should be considered when building new projects and migrating service from different service providers. As companies are trying to utilize cloud environments the knowledge about these might be lacking and thus increasing knowledge and introducing possible solutions is essential. This means that increasing knowledge about different approaches possible in cloud also different issues can be identified. Based on this kind of knowledge can the discussion about the possibility for utilizing cloud environments be improved. The use case for this study is the risk management and architecture design comparing of different cloud types and models based on a case study. Also, based on these different kinds of cloud types and models the security issues and countermeasures are discussed in a way that these measures could help to control or mitigate issues from happening. For finding feasible architecture designs these measures are to be considered alongside the responsibilities for different cloud models with the help of risk management. Risk management itself introduces risks and issues that are identified from cases and discussed as of how to control them within different cases. This thesis studies the possible issues and risks through a literature review that are associated with different cloud types and models. Also, introducing case study of three different cases that utilize these approaches and introduces such issues and risks associated with those cases. For identified issues and risks also relevant security methods and measures are studied through literature review and introduced to be utilized in risk management and architecture design. Based on these reviews a risk management is conducted to introduced cases where issues and risks are introduced with identification of real-world use case. Also, architecture design is introduced in a way that utilizes identified risks, control, and mitigation measures for protecting resources. What different possibilities and components to consider depending on different cases are also discussed as not all the risks can be mitigated with certain measures and would need more thought on as of what cloud type and model to utilize. Thesis also discusses about the three identified topics of risks, security measures and architecture and identifies relevant information from them for consideration. Thesis discusses about three different cases that were studied in a way as of how they differentiate from each other in the common field of risks, security measures and architecture design as they utilize the cloud in a different way. Discussion introduces the results and more detailed discussion that were identified from these three main topics. Detailed discussion itself contains similarities and differences identified from different cases and introduces more discussions based on those topics.
Keywords: Risk management, Architecture, Cloud security, Case study, IaaS, PaaS, SaaS